Electronic Medical Records in Colorectal Surgery - Turina, Matthias; Kiran, Ravi P. (Clinics in Colon and Rectal Surgery, 2013)
Electronic medical records (EMRs) are being widely implemented today, either as stand-alone applications in smaller practices or as systems-based integrated network solutions in larger health care organizations. Advantages include rapid accessibility, worldwide availability, ease of storage, and secure transfer of protected health information (PHI). Computerized physician order entry (CPOE) and decision-support capabilities such as the triggering of an alarm when multiple medications with known interactions are ordered, as well as the seemingly endless possibilities for electronic integration and extraction of PHI for clinical and research purposes, have created opportunities and pitfalls alike. Risks include breaches of confidentiality with a need to implement tighter measures for electronic security. These measures contrast efforts required for the realization of common data formats that have national and even international compatibility. EMRs provide a common platform that could potentially allow for the integration and administration of clinical care, research, and quality metrics, thus promoting optimal outcomes for patients. Technical and medicolegal difficulties need to be overcome in the years to come so that the safe use of PHI can be ensured while still maintaining the benefits and convenience of modern EMR systems.
Keywords: electronic medical record; protected health information; data; colorectal; colon; surgery; HIPAA; billing